The "untamed" /s/ of Italian dialects: An overview of the singular behaviour of Italo-Romance sibilants - Huszthy, Bálint (Verbum – Analecta Neolatina, 2017)
Sibilants cause several problems in phonology, especially /s/, and especially in Romance linguistics. This paper offers a general overview of the issue of preconsonantal /s/ in Italian dialects as far as its distributional problems are concerned. We will consider its position in the syllable, palatalisation processes, its behaviour in voice assimilation and its deletion. Special sections will be devoted to the case of “Neapolitan s”, which includes six allophones of the /s/ phoneme, and to an OT-account of /sC/-palatalisation in Italian dialects, which is an attempt of unifying theory in order to analyse different /sC/-palatalisation processes as a phonologically uniform phenomena.